UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING BAGI SISWA KELAS VI SDN 4 NGRAHO KEDUNGTUBAN BLORA - Nanik Maharani (Universitas PGRI Yogyakarta, 2018)
The purpose of this study is to improve the learning outcomes of IPA with learning modelSnowball Throwing in sixth grade students SDN 4 of Ngraho KedungtubanBlora. Thisresearch is classroom action research with sicth grader student research subects to 12students, consist of 5 male students and 7 female students. The research procedure uses fourstages of plan, action, observation and reflection. Data collection techniques in this study usesinstruments of data collection in the form of guidelines for observation, text guidelines,documentation and interview. Data analysis techniques in this study using the percentage ofstudent learning outcomes. The result in the study concluded of IPA with learning modelSnowball Throwing in sixth grade students SDN 4 of Ngraho Kedungtuban Blora.Improvement of learning outcomes can be seen from the increasing average of studentslearning outcomes and percentage. At pre cycle the average value of student learningoutcomes 56,7%, at I cycle the average value of student learning increasing become 59,2%,and at II cycle the average value of student learning increasing become 70,1%.The keys: The learning Snowball Throwing, learning outcomes of IPA